Estudio económico y social para el establecimiento de un comisariato popular orientado al buen vivir de los sectores pobres de la parroquia San Camilo, cantón Quevedo, año 2015 - Arce Banchón, Cynthia Carolina (2015)
This research project aims to assess the economic and social feasibility of the establishment of a popular oriented commissary good living of the poor of the parish San Camilo, Quevedo Canton in 2015. The urban parish San Camilo, has approximately fifty thousand inhabitants. This parish belongs to the canton Quevedo, Los Rios province, representing 28.57% of the total population of the city. In order to strengthen the good life and to promote the welfare, happiness and harmonious development between citizens and nature, it is essential to raise the present draft People's Commissariat, with the intention of strengthening savings and improve income their habitants. The research methodology was based on a population of 50,000 inhabitants of which a sample of 381 families that form survey was applied during the first half of 2015 was extracted unmet demand expressed by the consumption of food staples It is 3550 families and the project aims to meet 30% of this. Investment in fixed assets for the implementation of the Commissariat Popular is USD 60.770, deferred USD 1,514 and Working Capital USD 326.447 giving a total investment of USD 388.731 to be financed as follows: 70% with the contribution of partners and 30 % remaining through a bank loan. Project income amounted to USD 4, 525.355 annually, while expenditures are USD 3, 950.846, resulting in a net cash flow of USD 574.510 for the first year. With this investment, it is considered that the most favored genre with the jobs that will be created is the female, who absorb 75% and 25% male. The results through the financial indicators show that the project is feasible, because the NPV is USD + 3, 569,111.33, TIR148%, the cost benefit ratio of 1.13: and the payback period of investment is 3 months.